Normalisation of passivity during childbirth - positive experiences and trust in the healthcare system in serbia as generators of justifying passivity - Ninković Milica; Ilić Sandra; Damnjanović Kaja (Temida)
Research and practice show that within the healthcare system (HCS) in Serbia, women’s passivity during childbirth is normalised. Both HCS staff and female patients hold this representation of women as inherently passive. The paper aims to present research findings on passivity normalisation during childbirth. This study aimed to investigate the factors related to HCS experiences contributing to this passivity normalisation. Participants (N=363, 252 with childbirth experience) completed scales measuring trust in medical staff, distrust in the HCS, reliance on the HCS, frequency of positive and negative experiences with the HCS, and normalisation of passivity during childbirth. The examined factors accounted for 25% of the variance in normalising passivity during childbirth. Specifically, participants who were more reliant on the HCS, had given birth and reported more positive or fewer negative experiences, were more likely to normalise passivity. Paradoxically, a positive relationship with the HCS led to adopting the passivity norm, while negative experiences were a protective factor. The HCS appears to teach women passivity, as positive experiences within the system reinforce the perception of passivity as appropriate.